(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The railway is perceived as a modern, safe and environmentally sustainable way of transporting people and goods. In the past, appropriate innovations in the field of infrastructure and vehicles, combined with an attractive operational concept, have gradually become the backbone of public transport in the country. Even in this system, similar to other transport systems, there are accidents (events of emergency) or potentially risky situations. The paper places the issue of railway safety in the legislative context and uncovers the points of view from which the safety of railway traffic can be viewed.